The mediating role of health literacy on the relationship between health care system distrust and vaccine hesitancy during COVID-19 pandemic - Turhan, Zeynep; Dilcen, Hacer Yalnız; Dolu, İlknur (Current psychology (New Brunswick, N.J.), 2022)
This study explores the mediating role of health literacy on the association between health care system distrust and vaccine hesitancy. An online survey including Personal Information Form, Health Care System Distrust Scale, Vaccine Hesitancy Scale, and Health Literacy Scale were applied to 620 participants. The degree of applying mask-wearing, hygiene rule and physical distance, and the level of COVID-19 vaccine literacy were modeled with hierarchical multiple regression analysis to have a deeper analysis of participants’ actions towards COVID-19 vaccine hesitancy. It was found that health care system distrust and health literacy were the most important variables that had an impact on vaccine hesitancy. Based on the mediation analysis, the total effect of health care system distrust on vaccine hesitancy was statistically significant. Participants who held a low level of health literacy and a high perception of the health care system distrust experienced more vaccine hesitancy. The findings suggested the health literacy mediated the relationship between health care system distrust and vaccine hesitancy. Health authorities need to consider the dynamic and complex factors around the health care system distrust and health literacy to reduce vaccine hesitancy during COVID-19.